2016
DOI: 10.31018/jans.v8i3.1026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sowing dates and nitrogen levels on growth, yield and quality of scented rice cv. Pusa Sugandh-3 in Kashmir valley

Abstract: A field experiment was carried out to determine the optimum sowing date and nitrogen (N) level for the scented rice cv. Pusa Sugandh-3. Twelve treatment combinations of 3 sowing dates, viz., 15th, 16th and 18th standard meteorological week (SMW) at an interval of 10 days and 4 nitrogen levels (‘0’, ‘40’, ‘60’ and ‘80’ kg N ha-1) were tested randomized in split plot design with three replications. Significant highest plant height (98.56 cm), tillers m-2 (333.41), dry matter (98.38 q ha-1), panic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
4
10
0
Order By: Relevance
“…A linear negative correlation between sowing dates and growth period, in the later sowing dates was also reported by Peng-fei et al [14]. Wani et al [15], reported the days taken to reach flowering and harvest varied significantly among the sowing dates.…”
Section: Phenologysupporting
confidence: 75%
“…A linear negative correlation between sowing dates and growth period, in the later sowing dates was also reported by Peng-fei et al [14]. Wani et al [15], reported the days taken to reach flowering and harvest varied significantly among the sowing dates.…”
Section: Phenologysupporting
confidence: 75%
“…Basmati rice yield significantly increased from 1.7 t ha -1 (control) to a maximum of 9.4 t ha -1 (90 kg N ha -1 ) before declining to 5.8 t ha -1 (150 kg N ha -1 ) in the order: 0 < 30 < 60 < 150 < 120 < 90 kg N ha -1 respectively Moro et al, (2015). Similar findings are also confirmed Wani et al, (2016).…”
Section: Graded Levels Of Nitrogen On Growth Yield Quality and Economics Of Ricesupporting
confidence: 83%
“…The difference in the maturity time among tested cultivars were due to their genetical varietal characters. The early seeding of rice of all cultivars needing the maximum number of days may be due to sufficient temperature and adequate solar radiation during the growth period (Wani et al, 2016).…”
Section: Results and Discussion Effects Of Cultivars And Transplantin...mentioning
confidence: 99%